Pengaruh Konten Instagram @Folkative Terhadap Pemenuhan Kebutuhan Informasi Generasi Z - Setiawati, Sri Dewi; Herlambang, Zahra Khairunnissa (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The need for information has become increasingly important in society to meet various needs. With the advancement of technology, the Internet has transformed how people access information. Information can be easily accessed through the internet and social media platforms. Folkative is one of the popular Instagram accounts among the younger generation, serving as a digital source of up-to-date information. A distinctive feature of @folkative's content is its emphasis on text. Therefore, this study examines the influence of Instagram content from @folkative on fulfilling the information needs of Generation Z. The aim of this research is to determine the extent to which @folkative's Instagram content impacts the information needs of Generation Z. This research uses a quantitative approach with a descriptive research design. The sampling technique employed is purposive sampling, with a total of 400 respondents. Data analysis is conducted using simple linear regression, and hypothesis testing is performed through a T-test. The study is based on the Uses and Gratification theory, utilizing the model of media usage and effects. The results of this study indicate that @folkative's Instagram content influences the information needs of Generation Z by 60.3%, with the sub-variables of communication and context having the most significant impact. The remaining 39.7% is influenced by other factors.